TECHNOLOGY FALAFEL. AN ACTIVE HUMAN FACTOR IN THE HUMAN INFORMATION TECHNOLOGY SYSTEM - Mukhitdin Nazarov (Western European Studies, 2025)
The article titled "Active Human Factor in the Information Technology System" addresses some of the most pressing issues of today, such as the role of humans in the information world, the concept of information technologies, and the issues of their rational use. It is emphasized that technologies are increasingly becoming an integral part of the productive forces of society, with particular attention given to the importance of the human factor and its active involvement in this process.
Keywords: Information technology; philosophy of technology; human factor